The use of games in teaching selected topics in college chemistry - Dimagiba, Elyn Macalisang (Animo Repository, 1997)
This study focuses on the effects of using games in teaching selected topics in college chemistry. The effects were determined in terms of significant difference in attitude and achievement between first year college engineering students who were taught selected chemistry topics using games as instructional aid and those who were taught by the conventional method. The significant difference in achievement between students of different mental ability levels, the interaction effect between method of instruction and mental ability level, and the correlation between attitude and achievement were also determined. Four intact classes of 81 students were involved in the study (41 students in the experimental group and 40 students in the control group). These students were enrolled in Chem III (General and Inorganic Chemistry I) in the first semester of school year 1997-98 in Notre Dame University, Cotabato City. The study utilized the non-equivalent control group design (quasi-experimental). A 20-item chemistry attitudinaire and a 65-item chemistry achievement test constructed by the researcher were used as instruments in the study. These instruments served as both the pretest and the posttest. The data collected on students' attitude were subjected to t-test for dependent samples. Students' achievement data were treated using analysis of covariance with the pretest and entrance examination as covariates and the posttest as the criterion measure. Partial correlation were applied on students' attitude and students' achievement with t-test of significance. All tests of significance were determined at the .05 level of significance.The findings of the study revealed that:1. There was no significant difference in attitude towards chemistry between students in the experimental group and those in the control group.2. Students in the experimental group significantly performed better than those in the control group.3. There was no significant difference in the achievement in chemistry between above average and below average students.4. There was no significant interaction effect between method of instruction and students' ability groupings.5. There was no significant relationship between students' attitude and achievement.From the findings of the study, it could be concluded that the use of games in teaching chemistry has no significant effect on the students' attitude towards the subject the use of games enhances the achievement of students on the subject above average students do not differ in performance with below average students the teaching method in chemistry is not affected by students' ability groupings and students' attitude towards chemistry is not associated with students' achievement on the subject.